Disruptive technologies and career transition strategies of middle-skilled workers. Issue 5 (9th September 2019) - Chen, Quan; Wang, Jing-An; Ou, Ruiqiu; Sun, Junhua; Chang, Li-Chung
Abstract : Purpose: Disruptive technologies often disrupt the careers of middle-skilled workers. The purpose of this paper is to investigate career transition strategies of middle-skilled workers that partially continue or expand their careers under the condition of disruptive technologies. Design/methodology/approach: This paper established a conceptual framework of career transition strategies for middle-skilled workers by integrating the existing studies of disruptive technologies, technological trajectory transition, boundaryless and protean careers, and careers as repositories of knowledge. Findings: The authors proposed three types of career transition strategies to partially prolong middle-skilled workers' careers, namely, industry-oriented transition strategy which refers to a transfer to other occupations in the original industry, technology-oriented transition strategy which refers to a transfer to occupations with original technical skills in other industries, and comprehensive transition strategy which refers to a transfer to other occupations in the related industries. Further, this paper discusses the external conditions and individual competencies for each career transition strategy, and timing for implementing a career transition strategy from the perspective of the technology life cycle. Originality/value: This paper focused on sustainable careers of middle-skilled workers under the condition of disruptive technologies, which received very little attention from the current literature. The findings also suggested for middle-skilled workers to develop a sustainable or long-term career in the current era of many disruptive technologies. The findings may also imply on how firms and government should contribute to help workers on handling scenarios of technological disruption.